Association of mammography with sociodemographic and care factors in residents of Belo Horizonte, MG, Brazil - Magalhães, Amanda Silva; Moreira, Bruno de Souza; Costa, Dário Alves da Silva; Andrade, Amanda Cristina de Souza; Caiaffa, Waleska Teixeira (Mastology, 2020)
Objective: This study aimed to investigate screening mammography in the last two years, sociodemographic factors, and healthcare service use among women aged 40–69 years living in a Brazilian urban center. Methods: The data are part of a household survey called “MOVE-SE Academias” (2014/2015) carried out in Belo Horizonte (MG). The sample was selected using a stratified three- stage cluster sampling: Health Academy Program units distributed in the city, census tracts, and households. Pearson’s chi-square test was used in the analysis. Results: Of the 371 women included in this study with a mean age of 52.5 years, 66.2% among those aged 40–49 years (n = 157) and 75.7% among those aged 50–69 years (n = 214) reported being submitted to mammography within two years before the interview. When it comes to women aged 40–49 and 50–69 years, a higher proportion was found among those with higher schooling (p = 0.011 and p = 0.001), who had been to medical appointments in less than one year (p = 0.024 and p < 0.001), who had performed the Pap smear test in less than two years (p < 0.001 for both groups) and who reported having a private health insurance (p = 0.007 and p = 0.008). Higher family income was associated only with the performance of the screening exam among women aged 40–49 years (p = 0.006). Conclusion: Our results suggest inequalities in access to health services for breast cancer screening, modulated by socioeconomic factors, including private health insurance. Prioritizing more vulnerable groups in cancer screening as a public policy can contribute to reducing health inequalities.